Stem Cell Therapy for Ischaemic Stroke: Translation from Preclinical Studies to Clinical Treatment - Balami, Joyce S.; Fricker, Rosemary A.; Chen, Ruoli (CNS & Neurological Disorders - Drug Targets, 2013)
No pharmacological intervention has been shown convincingly to improve neurological outcome in stroke patients after the brain tissue is infarcted. While conventional therapeutic strategies focus on preventing brain damage, stem cell treatment has the potential to repair the injured brain tissue. Stem cells not only produce a source of trophic molecules to minimize brain damage caused by ischaemia/reperfusion and promote recovery, but also potentially turn to new cells to replace those lost in ischaemic core. Although preclinical studies have shown promise, stem cell therapy for stroke treatment in human is still at an early stage and it is difficult to draw conclusions from current clinical trials about the efficacy of the different treatments used in humans. This article reviews the potential of various types of stem cells, from embryonic to adult to induced pluripotent stem cells, in stroke therapy, highlights new evidence from the ongoing clinical trials and discusses some of the problems associated with translating stem cell technology to a clinical therapy for stroke.
Keywords: endogenous